Granulocyte-Macrophage Colony-Stimulating Factor Priming plus Papillomavirus E6 DNA Vaccination: Effects on Papilloma Formation and Regression in the Cottontail Rabbit Papillomavirus-Rabbit Model - Leachman, Sancy A. (American Society for Microbiology, 2000)
A cottontail rabbit papillomavirus (CRPV) E6 DNA vaccine that induces significant protection against CRPV challenge was used in a superior vaccination regimen in which the cutaneous sites of vaccination were primed with an expression vector encoding granulocyte-macrophage colony-stimulating factor (GM-CSF), a cytokine that induces differentiation and local recruitment of professional antigen-presenting cells. This treatment induced a massive influx of major histocompatibility complex class II-positive cells. In a vaccination-challenge experiment, rabbit groups were treated by E6 DNA vaccination, GM-CSF DNA inoculation, or a combination of both treatments. After two immunizations, rabbits were challenged with CRPV at low, moderate, and high stringencies and monitored for papilloma formation. As expected, all clinical outcomes were monotonically related to the stringency of the viral challenge. The results demonstrate that GM-CSF priming greatly augmented the effects of CRPV E6 vaccination. First, challenge sites in control rabbits (at the moderate challenge stringency) had a 0% probability of remaining disease free, versus a 50% probability in E6-vaccinated rabbits, and whereas GM-CSF alone had no effect, the interaction between GM-CSF priming and E6 vaccination increased disease-free survival to 67%. Second, the incubation period before papilloma onset was lengthened by E6 DNA vaccination alone or to some extent by GM-CSF DNA inoculation alone, and the combination of treatments induced additive effects. Third, the rate of papilloma growth was reduced by E6 vaccination and, to a lesser extent, by GM-CSF treatment. In addition, the interaction between the E6 and GM-CSF treatments was synergistic and yielded more than a 99% reduction in papilloma volume. Finally, regression occurred among the papillomas that formed in rabbits treated with the E6 vaccine and/or with GM-CSF, with the highest regression frequency occurring in rabbits that received the combination treatment.